2008
DOI: 10.1007/s11666-008-9228-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Conductive Flame Sprayed Aluminum Coatings on Textile Substrates

Abstract: In this study, electrically conductive and flexible aluminum coatings using powder and wire flame spraying were successfully deposited onto diverse textiles. The influences of various process parameters and fabric materials on the electrical conductivity and microstructure of the metal-fabric composites were investigated. Preliminary results show that to obtain excellent coating surface conductivity values a specific coating quantity of higher than 20 mg/cm 2 is required. After further optimization of the spra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 2 publications
0
22
0
Order By: Relevance
“…successfully managed to deposit aluminium on fabric materials by using flame spray [12]. It was possible to achieve coating conductivity, despite the high level of internal porosity.…”
Section: -Introductionmentioning
confidence: 99%
“…successfully managed to deposit aluminium on fabric materials by using flame spray [12]. It was possible to achieve coating conductivity, despite the high level of internal porosity.…”
Section: -Introductionmentioning
confidence: 99%
“…3, the metal coating and the granular particles used for roughening the polymer-based substrate are bound by mechanical interlocking. On the other hand, the deposition of thermally sprayed coatings onto polymer-based substrates without surface preparation has also been reported in the literature ( Ref 21,25,40,47,68). In cold spraying, the sprayed particles were heated to temperatures below the melting temperature of the powder material.…”
Section: Surface Preparation Of Polymer-based Substratesmentioning
confidence: 96%
“…Voyer et al (Ref 34,40) showed that the surface conductivity of Al coatings deposited onto polyester textile substrates increased proportionally to the coating thickness, while the flexibility of the polymer fabric was retained and was unchanged. Boyer et al (Ref 53) characterized flame-sprayed Al-12Si coatings deposited onto PU substrates.…”
Section: Flame Sprayingmentioning
confidence: 99%
“…Aluminum powders were not taken into account since it had been reported earlier that the use of wires produced coatings having higher specific electrical conductivities than those obtained while using powders (Ref 24,25). The spray gun was mounted on a six-axis robot (ABB, Model IRB2400/S4C, Vä sterå s, Sweden), while the fabric substrate was maintained in a fixed position during the spray process.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…The specific surface electrical conductivities (S A ) of the different coated fabrics were measured using a selfdeveloped 4-points surface conductivity measurement setup, as shown in Since the aim of this study is to demonstrate the possibility of producing flexible batteries out of aluminumcoated textiles using the flame spray process, the reader is referred to the studies published earlier by the author to have a much profound insight on the optimization procedure of the spray parameters (Ref 24,25). For clarity purposes, only a brief overview of the spray parameters and their optimization and of the textile materials used will be given here.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%